Synthesis, Characterization of Coumarin-Chalcone Hybrid Compounds and Evaluation as Fungicidal Against Fungal Contamination of In vitro Culture of Date Palm Phoenix dactylifera L. - Jassim, Naji Salim; Aldosary , Naser H.; Jaafer, Mahmood Oda (Basrah Journal Of Date Palm Research, 2024)
This study involved the synthesis and structural characterization of Coumarin-containing chalcone derivatives as a fungicide. Several spectroscopic techniques, including FTIR, 1H NMR, and 13C NMR, were used to confirm their structures. The coumarin-chalcone hybrid compounds were tested in vitro for their ability to reduce the main contaminating fungi that infest in vitro culture labs. According to the study’s findings, the PDA medium supplemented with 1.5 and 2 mg/L concentrations of all synthesis of coumarin-chalcone derivatives showed no signs of contaminating fungi. While the concentration of 1.0 mg/L showed weak inhibition, compared to the growth of fungi in the control treatment (not treated with chalcone derivatives), in which the diameter growth of the contaminated fungi reached 9 cm (100%). In addition, it was found that, in comparison to the control, the cultures treated with chalcone derivatives over longer periods showed a trend toward decreased and delayed biomass production. Compared to controls, coumarin-chalcone hybrid treatments at 1.5 and 2.0 mg/L did not result in fungal contamination in vitro culture experiments. Furthermore, the result of the in vitro culture experiment of date palm found the multiplication rate of shoots enhanced in MS supplemented with coumarin-chalcone hybrids at a concentration of 1.5 mg/L increased considerably to 32.24%, compared with 12.33% in the control. The results of this investigation will offer practical recommendations for lowering or removing the risk of fungal contamination by applying Coumarin-Chalcone Hybrid as an environmentally friendly fungicide.